Developments in Diagnosis and Antileishmanial Drugs - Bhargava, Prachi; Singh, Rajni (Interdisciplinary Perspectives on Infectious Diseases, 2012)
Leishmaniasis ranks the third in disease burden in disability-adjusted life years caused by neglected tropical diseases and is the second cause of parasite-related deaths after malaria; but for a variety of reasons, it is not receiving the attention that would be justified seeing its importance. Leishmaniasis is a diverse group of clinical syndromes caused by protozoan parasites of the genus Leishmania. It is estimated that 350 million people are at risk in 88 countries, with a global incidence of 1–1.5 million cases of cutaneous and 500,000 cases of visceral leishmaniasis. Improvements in diagnostic methods for early case detection and latest combitorial chemotherapeutic methods have given a new hope for combating this deadly disease. The cell biology of Leishmania and mammalian cells differs considerably and this distinctness extends to the biochemical level. This provides the promise that many of the parasite’s proteins should be sufficiently different from hosts and can be successfully exploited as drug targets. This paper gives a brief overview of recent developments in the diagnosis and approaches in antileishmanial drug discovery and development.